Recent advances in computational modeling of fibrin clot formation: A review. (December 2019) - Yesudasan, Sumith; Averett, Rodney D.
Graphical abstract: Schematic of various modeling approaches. (a) In continuum length and time scales, NS equations are solved to obtain the velocity field. (b) CDR equations provide the solutions as the concentration of various blood factors and their reactions. (c) Clot formation using mesoscopic methods such as DPD, CGMD or CPM. (d) MD simulations or Ab-Initio methods used to capture atomic level biomolecular interactions. Highlights: Computational strategies at various length scales are crucial for the field of thrombosis and hemostasis Continuum methods alone cannot describe thrombosis and hemostasis physically Hematological pathologies can be elucidated using various computational techniques Complex multiscale methods will be necessary for understanding thrombosis and hemostasis in the future Abstract: The field of thrombosis and hemostasis is crucial for understanding and developing new therapies for pathologies such as deep vein thrombosis, diabetes related strokes, pulmonary embolisms, and hemorrhaging related diseases. In the last two decades, an exponential growth in studies related to fibrin clot formation using computational tools has been observed. Despite this growth, the complete mechanism behind thrombus formation and hemostasis has been long and rife with obstacles; however, significant progress has been made in the present century. The computational models and methods used in this context are diversified into different spatiotemporal scales, yet there is no single model which can predict both physiological and mechanical properties of fibrin clots. In this review, we list the major strategies employed by researchers in modeling fibrin clot formation using recent and existing computational techniques. This review organizes the computational strategies into continuum level, system level, discrete particle (DPD), and multi-scale methods. We also discuss strengths and weaknesses of various methods and future directions in which computational modeling of fibrin clots can advance.